Overall Downregulation of mRNAs and Enrichment of H3K4me3 Change Near Genome-Wide Association Study Signals in Systemic Lupus Erythematosus: Cell-Specific Effects - Zhang, Zhe; Shi, Lihua; Song, Li; Maurer, Kelly; Petri, Michele A.; Sullivan, Kathleen E. (Frontiers in Immunology, 2018)
This study was designed to define gene expression and H3K4me3 histone modifications in T cells, B cells and monocytes in systemic lupus erythematosus (SLE). Array studies of total peripheral blood mononuclear cells have demonstrated gene expression signatures related to neutrophils, interferon and other inflammatory pathways. It is not clear how consistent these effects are across different cell types. In this study, RNA-seq and ChIP-seq were utilized to identify gene expression patterns and H3K4me3 histone modifications related to promoter activation in SLE. Across the three cell types, there was 55% concordance for gene expression changes related to SLE. Key conserved pathways were ribosome biogenesis among up-regulated genes and heat shock response among down-regulated genes. ETS family transcription factors and STAT1 were revealed as common regulators by position weight matrices. When epigenetic changes were leveraged with gene expression, the pivotal transcription factors ATF3 and FOS were defined with ATF3 also cross referencing with gene expression-identified transcription factors. Genome-wide association study (GWAS) single nucleotide polymorphisms associated with SLE were cross referenced with both mRNA and H3K4me3 changes in SLE. Baseline mRNA expression and H3K4me3 peak height was higher at sites that cross referenced with GWAS signals, however, all three cell types exhibited an overall decrease in expression of GWAS-associated RNAs differentially expressed in SLE. H3K4me3 changes in SLE were also enriched in GWAS-associated sites. In summary, the SLE disease process is associated with both shared and cell-specific changes in gene expression and epigenetics. Surprisingly, GWAS-associated RNAs were overall markedly decreased across all three cell types. Transcription factor analysis identified ATF3, FOS, STAT1 and ETS family members as critical, all pathways with a recognized relationship to the SLE disease process. GWAS signals clearly mark both cell-type specific changes in SLE as well as concordant changes across all three cell types. Interpretation of single nucleotide polymorphism effects in SLE will require tissue-specific mechanistic studies and therapeutics will require mechanistic studies in multiple cell types.